2017
DOI: 10.1242/dev.150532
|View full text |Cite
|
Sign up to set email alerts
|

Clasp2 ensures mitotic fidelity and prevents differentiation of epidermal keratinocytes

Abstract: Epidermal homeostasis is tightly controlled by a balancing act of selfrenewal or terminal differentiation of proliferating basal keratinocytes. An increase in DNA content as a consequence of a mitotic block is a recognized mechanism underlying keratinocyte differentiation, but the molecular mechanisms involved in this process are not yet fully understood. Using cultured primary keratinocytes, here we report that the expression of the mammalian microtubule and kinetochoreassociated protein Clasp2 is intimately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A recent study showed that CLASP2 is intimately associated with the basal proliferative make up of keratinocytes. 39 Therefore, our in vivo study results might reflect the effects of CLASP2 on keratinocyte migration, as well as its proliferation during the wound healing process. We demonstrated that CLASP2 is an effective mediator of keratinocyte migration, which plays a very important role in the primary wound healing process and is initiated by wound contraction.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A recent study showed that CLASP2 is intimately associated with the basal proliferative make up of keratinocytes. 39 Therefore, our in vivo study results might reflect the effects of CLASP2 on keratinocyte migration, as well as its proliferation during the wound healing process. We demonstrated that CLASP2 is an effective mediator of keratinocyte migration, which plays a very important role in the primary wound healing process and is initiated by wound contraction.…”
Section: Discussionmentioning
confidence: 94%
“…CLASP2 has been associated with migratory and microtubule stabilization in several studies involving epidermal cells, fibroblasts, and neuronal dendrites. 33,39 It is very likely that this interactive mechanism is Figure 10. Schematic diagram of possible interactions between CLASP2 related factors, such as CLIP-170, EB1, and IQGAP-1, and the AKAP220 complex.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence emerges connecting DNA damage and aneuploidy with reduced self-renewal capacity and increased differentiation in flies 29 and mammals 30,31 . Recent studies in mouse skin and cultured keratinocytes associated DNA damage accumulation with keratinocyte differentiation 6,32 .…”
Section: Low Contractility Upon Par3 Loss Drives Ectopic Differentiatmentioning
confidence: 99%